PRE-WAR AND WAR-TIME CONFLICT MANAGEMENT STRATEGIES OF THE NIGERIAN CIVIL WAR (2015)
Nigeria experienced a civil war between 1967 and 1970 which claimed millions of lives on the Federal and Biafran sides. Studies exist on trend, execution and termination of the war but the pre-war and war time conflict management strategies have not been fully explored. This study therefore, examined the strengths and weaknesses of the various management strategies adopted by the conflict parties prior to the outbreak of hostilities as well as those employed during the war with a few to identifying lessons derived from the management strategies. The study adopted a qualitative approach, utilising a combination of descriptive and case study research designs. Data were obtained from primary and secondary sources. A total of six in-dept interviews were conducted with surviving war-time key actors and stakeholders from the Federal and Biafran sides. Two Focus Group Discussions were held in Enugu and Kaduna with war veterans. Archival materials were also consulted. Secondary data were collected from war-time memoirs, minutes of the Aburi accord, decrees, edicts and newspaper publications. A combination of content and descriptive mode of data analysis was employed. A mix of joint-problem solving and third party intervention strategies such as conciliation and mediation were adopted before the war commenced. The failure of these strategies to transform the conflict accounted for the optional strategy of confrontation and strategic withdrawal as the last resort. The leaders and parties to the conflict did not adopt compromise, cooperation and avoidance, but opted for competition as an alternative to joint problem solving. The inability to strike a balance between the cooperative and competitive orientation by the Biafran leader was fundamental to the failure of local and international concerted efforts to transform the conflict peacefully. This attitude made the 30 months war not only inevitable, but also unduly prolonged with devastating impact on both human and material resources. These were further complicated by the disposition of some of the mediators which created distrust between the disputing parties. The lessons from the conflict management strategies of the war are that the parties to the conflict were invariable not very experienced in understanding that the cost of war is enormous and more devastating than peace, which creates room for accommodation and joint problem solving. Also, strategic scenario analysis should include best, middle and worst case scenarios before making violent confrontation an option in any conflict. The pre-war and war-time conflict management strategies of the Nigerian civil war failed to achieve the desired result mainly because of the attitude and disposition of parties to the conflict. Leaders, therefore, need to be skilled in conflict management while dealing with intractable conflicts, so as to prevent its escalation. Efforts at peaceful management of conflicts should include compromise, accommodation, open-mindedness, trust and respect for human dignity.